Salt intake and blood pressure response to percutaneous renal denervation in resistant hypertension - Beus, Esther; Jager, Rosa L.; Beeftink, Martine M.; Sanders, Margreet F.; Spiering, Wilko; Vonken, Evert‐Jan; Voskuil, Michiel; Bots, Michiel L.; Blankestijn, Peter J.; Elgersma, O; IJsselmuiden, AJJ; Valk, PHM; et al. (The journal of clinical hypertension (Greenwich, Conn.), 2017)
The effect of lowering sympathetic nerve activity by renal denervation (RDN) is highly variable. With the exception of office systolic blood pressure (BP), predictors of the BP‐lowering effect have not been identified. Because dietary sodium intake influences sympathetic drive, and, conversely, sympathetic activity influences salt sensitivity in hypertension, we investigated 24‐hour urinary sodium excretion in participants of the SYMPATHY trial. SYMPATHY investigated RDN in patients with resistant hypertension. Both 24‐hour ambulatory and office BP measurements were end points. No relationship was found for baseline sodium excretion and change in BP 6 months after RDN in multivariable‐adjusted regression analysis. Change in the salt intake–measured BP relationships at 6 months vs baseline was used as a measure for salt sensitivity. BP was 8 mm Hg lower with similar salt intake after RDN, suggesting a decrease in salt sensitivity. However, the change was similar in the control group, and thus not attributable to RDN.